Analisis Yuridis Penerbitan Surat Persetujuan Berlayar Mt. Sea Tanker Ii di Kantor Kesyahbandaran dan Otoritas Pelabuhan Batam - Rahma, Isnawati Azizatul; Situmeang, Ampuan; Girsang, Junimart (Universitas Batanghari Jambi, 2023)
MT. Sea Tanker II, which was going to docking to Surabaya, was hampered by its departure due to the non-issuance of a Sailing Approval Letter by the KSOP Batam Region, on the grounds that the owner MT. Sea Tanker II was reported by other parties regarding MT. Sea Tanker II at the Riau Islands Police. MT. Sea Tanker II has carried out its obligations to pay the fees for anchoring services, mooring services, guide-in services, and delay-in services, as well as completing the required documents for the issuance of the Sailing Approval Letter, but the Special KSOP Batam Region is not willing to issue the SPB for fear of being investigated by investigators from the Regional Police. Riau Islands. The actions taken were not in accordance with the KSOP authority contained in articles 207 and 208 point (g) of Law Number 17 of 2008 concerning Shipping, which states that KSOP Batam Region can only detain ships with a written order from the Court. This research is a legal research, namely the process of finding legal rules, legal principles, or legal doctrine in order to answer legal issues and analyze court decisions.